Biohybrid plants with electronic roots via in vivo polymerization of conjugated oligomers. Issue 12 (3rd November 2021) - Parker, Daniela; Daguerre, Yohann; Dufil, Gwennaël; Mantione, Daniele; Solano, Eduardo; Cloutet, Eric; Hadziioannou, Georges; Näsholm, Torgny; Berggren, Magnus; Pavlopoulou, Eleni; Stavrinidou, Eleni
Abstract : Conjugated oligomers polymerize in vivo on the root system of intact plants forming an extended network of tissue integrated conductors while the plants continue to grow and develop. The conducting roots are used to store energy in the plant. Abstract : Plant processes, ranging from photosynthesis through production of biomaterials to environmental sensing and adaptation, can be used in technology via integration of functional materials and devices. Previously, plants with integrated organic electronic devices and circuits distributed in their vascular tissue and organs have been demonstrated. To circumvent biological barriers, and thereby access the internal tissue, plant cuttings were used, which resulted in biohybrids with limited lifetime and use. Here, we report intact plants with electronic functionality that continue to grow and develop enabling plant-biohybrid systems that fully maintain their biological processes. The biocatalytic machinery of the plant cell wall was leveraged to seamlessly integrate conductors with mixed ionic–electronic conductivity along the root system of the plants. Cell wall peroxidases catalyzed ETE-S polymerization while the plant tissue served as the template, organizing the polymer in a favorable manner. The conductivity of the resulting p(ETE-S) roots reached the order of 10 S cm −1 and remained stable over the course of 4 weeks while the roots continued to grow. The p(ETE-S) roots were used to build supercapacitors that outperform previous plant-biohybrid charge storage demonstrations. Plants were not affected by the electronic functionalization but adapted to this new hybrid state by developing a more complex root system. Biohybrid plants with electronic roots pave the way for autonomous systems with potential applications in energy, sensing and robotics.